CHANGING ENGLISH TEACHING ERA IN HIGHER EDUCATION THROUGH EXPERIENTIAL LEARNING - Mudra, Heri (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2016)
Experiential Learning (EL) has become one of a modern method implemented in ELT contexts. The use of this method has benefited both English teachers and learners in some contexts. EL method is implemented based on learners` experiences. The experiences can lead the learners to a practical knowledge that is needed for their future teaching experiences. To sum up, EL method covers all aspects of teaching and learning.